Quantitation by Portable Gas Chromatography: Mass Spectrometry of VOCs Associated with Vapor Intrusion - Justin D. Fair; William F. Bailey; Robert A. Felty; Amy E. Gifford; Benjamin Shultes; Leslie H. Volles (International Journal of Analytical Chemistry)
Development of a robust reliable technique that permits for the rapid quantitation of volatile organic chemicals is an important first step to remediation associated with vapor intrusion. This paper describes the development of an analytical method that allows for the rapid and precise identification and quantitation of halogenated and nonhalogenated contaminants commonly found within the ppbv level at sites where vapor intrusion is a concern.